2017
DOI: 10.1159/000480427
|View full text |Cite
|
Sign up to set email alerts
|

Combined Impact of Telomere Length and Mitochondrial DNA Copy Number on Cognitive Function in Community-Dwelling Very Old Adults

Abstract: Background: This study was conducted to investigate the combined impact of telomere length and mitochondrial DNA (mtDNA) copy number on cognitive function in community-dwelling very old adults. Methods: In total, 186 subjects over 75 years participated in this study. Cognitive function was assessed using the Korean Mini-Mental State Examination, and leukocyte telomere length and mtDNA copy number were measured using real-time polymerase chain reaction methods. Results: Both the fourth quartile of telomere leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…These aging-related neurodegenerative diseases have all underlying mitochondrial pathologies [57][58][59][60] and dysregulated ubiquitination pathways [61]. In particular, mtDNA-CN has been implicated in Alzheimer's disease [62][63][64] and cognitive function [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…These aging-related neurodegenerative diseases have all underlying mitochondrial pathologies [57][58][59][60] and dysregulated ubiquitination pathways [61]. In particular, mtDNA-CN has been implicated in Alzheimer's disease [62][63][64] and cognitive function [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Common pathways and complicated telomere-mitochondria interplay during human ageing were also suggested, although the relationship is still not completely understood [31]. A recent report investigating the combined impact of telomere length and mtDNAcn on cognitive function of communitydwelling very old adults proposed that the combination of the two parameters might be useful for monitoring cognitive decline in older people [7]. The promise of using mtDNAcn and TL as combined biomarkers of health and disease in the future prompted us to investigate their association in the framework of a genetically controlled study design, while also assessing co-twin similarities of monozygotic and dizygotic twin subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence suggested that mitochondrial biogenesis could be modulated by the telomere – p53–PPARG (peroxisome proliferator-activated receptor γ) axis, and also by the telomerase enzyme, but the exact mechanisms are still unknown [ 7 , 48 , 49 ]. Along with in vitro and animal models aiming to reveal the molecular mechanisms underlying the associations of telomere and mitochondrial functions, recent population-based studies have started to investigate the connection between mtDNAcn and TL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations